Research on the Development of Edu Games as Learning Media for Geometry and Arithmetic in Elementary School Children - Ridwan, Taufik; Hidayat, Endang; Hikmawan, Rizki; Andrian, Rian; Yasin, Aldi (International Conference on Elementary Education, 2021)
Mathematics is a discipline science that has many influences on the theoretic in the classroom and the practice in everyday life. Some of the branches of mathematics that are important in elementary school are geometry and arithmetic. Along with the development of information and communication technology, the development of mathematics learning has also developed. This research tries to discuss and analyze the development of Edu games that can be used for learning geometry and arithmetic. The research method used in this research is the descriptive analysis method. As a result, educational games for geometry and arithmetic developed from conventional games (played through movements) and games in digital form. Digital games are also growing, starting from using computers, smartphones, to adding augmented reality